Earthquake preparedness of households in Jeddah, Saudi Arabia: a perceptual study. (2nd July 2016) - Azim, Mohammad Tahlil; Islam, Mohammad Mazharul
ABSTRACT: This is a pioneering perceptual study on earthquake preparedness of households in the context of Jeddah, Saudi Arabia. It measures the level of preparedness as well as some perceptual issues like outcome instrumentality, risk perception, and causal attribution related to the preparation for earthquake. An attempt is also made to explore the effect of gender, age, education and home ownership on respondents' perceptions and preparation. The study used data from 555 respondents collected through a structured questionnaire. Descriptive statistics as well as independent sample T -test and Estimated logistic model were used to analyze the data. Overall, the residents of Jeddah perceive low risk of earthquake and hence are not well prepared for it. Their perception is somewhat influenced by their religious and cultural upbringing. However, they are not observed to be fanatic; rather, they maintain a sense of pragmatism in their belief and attitude toward earthquake. Thus, it shows a fertile ground for nurturing a community-based approach for hazard mitigation. Education also plays a positive role in preparing for earthquake.